ANALYSIS AND DESIGN OF USER INTERFACE ON E-LEARNING APPLICATION OF SMK NEGERI 12 SURABAYA WITH USER CENTERED DESIGN METHOD - Habiburrohman Habiburrohman; Endra Rahmawati; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
SMK Negeri 12 Surabaya is one of the vocational schools in Surabaya that focuses on the arts. The location of SMK Negeri 12 Surabaya is on Jl. Siwalankerto Permai No. 1 Surabaya. With the Covid-19 pandemic, the whole world has made their activities run online. One of the distance learning methods applied by SMK Negeri 12 Surabaya is to use the E-Learning application in the teaching and learning process between teachers and students. E-Learning is one form of using the internet in improving the learning process through cyberspace. Based on the results of a questionnaire involving teachers and students as respondents in this study, the problem that occurs is that teachers have difficulty in conveying material to giving assignments to students. So that students do not receive material and task information properly and cause students not to get the information correctly and late such as learning materials, assignments, to lesson schedules. This study aims to provide recommendations for designing user interfaces for E-Learning applications used in SMK Negeri 12 Surabaya. The result of this research is a user interface design that is made based on the steps contained in the User-Centered Design (UCD) method by carrying out six steps namely, Plan the user centered design process, Understand and specify the context of use, specify user and organization requirements, Produce design solutions, and Evaluate design against user requirements. The results of this research evaluation use the Website Usability Evaluation Tool (WEBUSE) which has four categories, namely Content, Organization, and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness with an average point value of 0.610 with a usability level. "Good" means that the E-Learning application at SMK Negeri 12 Surabaya can already be used by teachers and students quite well.